Insights into the systematics of the family Ophryoscolecidae (Ciliophora, Entodiniomorphida). (20th May 2022) - Cedrola, Franciane; Senra, Marcus Vinicius Xavier; Fregulia, Priscila; D'Agosto, Marta; Dias, Roberto Júnio Pedroso
Abstract: The family Ophryoscolecidae currently comprises 225 species of trichostomatid ciliates, subdivided into three subfamilies (Entodiniinae, Diplodiniinae, and Ophryoscolecinae). The last taxonomic review of the family was performed 55 years ago, but recent morphological and molecular studies indicate the need for a profound review of the systematics of this taxon, since its current taxonomy is insufficient to organize the diversity of the group. Here, we briefly review the systematics of the family Ophryoscolecidae based on information recovered from the literature and new morphological and molecular data. We add four new 18S rDNA sequences of ophryoscolecids to molecular databases, which contributed to improving the comprehension of intrafamily relationships within this group. Finally, we discuss some systematic problems and suggest approaches to resolve such inconsistencies in the future.